Penerapan Lesson Study Pembelajaran Matematika Menggunakan Model Pembelajaran Problem Based Learning (PBL) Pada Materi Matriks - Nugroho, Zudha Basofi; Nurhayati, Siti; Suryaningsih, Wiwit; Sukiran, Sukiran (Litbang PWM Jawa Tengah, 2023)
Mathematics is a field of science that is taught from elementary school to university level. The matrix is one of the mathematics materials taught in XI class. In this material, students have difficulty understanding the concept of matrix operations, especially multiplication operations, so an effort is needed to improve students' understanding of matrix material. This research uses a descriptive analysis method with a qualitative approach. The conclusion of this research is the implementation of lesson study using the PBL learning model is in accordance with the stages in lesson study, namely planning, implementation, and reflection. It stages can improve the ability of students to understand the matrix material. In addition, through the implementation of the PBL learning model, learning activities become more fun and can foster the creative, democratic, and curious character of students.